Structural Investigation of Granular Composites by Modern Methods - Ráthy, Istvánné; Pinke, Péter; Fábián, Enikő Réka; Nagyné Halász, Erzsébet (International Journal of Engineering and Management Sciences, 2020)
Structural investigations of polymer-based particulate composites were carried out using modern test methods. We had composite sheets with different compositions and different injection molding speeds. In the polypropylene matrix, three types of glass beads were mixed in three weight percentages. In our investigations, the granular composites were studied with a widely used examination equipment, scanning electron microscope (SEM) and industrial computer tomography (CT) as a modern diagnostic tools. The purpose of the study was to investigate the distribution and interfacial adhesion of glass beads.